LAND FRAGMENTATION AND RURAL SUSTAINABILITY IN BADE LOCAL GOVERNMENT AREA, YOBE STATE, NIGERIA - Abba Saleh; Mohammad Rafee Majid; Zainab Toyin Jagun, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Land is one of the major factors in agricultural and other production activities which its accessibility and utilisation affect the outcome, especially in rural areas. This paper analyses land fragmentation and Rural Sustainability in Bade LGA, Yobe State, Nigeria. Identify rural social sustainability factors in the study area and examine the relationship between land fragmentation and rural sustainability to recommend the best possible land-based rural sustainability practice. The survey method was administered to a random sample of household heads in the study area. Simpson Index, Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and Partial Least Square- Structural Equation Modelling (PLS-SEM) was used to analyse the data. Thus, the results revealed the extent of land fragmentation in the study areas (Î²=-0.076, t=1.074; p > 0.05). The results of Exploratory Factor Analysis (EFA) showed that all the 18 causes of the extent of land fragmentation have factor loadings ranges from 0.760- 0.978. Hence, these analysis factors are considered the key causes of land fragmentation in the study area. PLS-SEM findings highlighted a significant alignment between land fragmentation, causes, and rural sustainability, all of which formed the basis for developing the conceptual framework for mitigating land fragmentation challenges. The conceptual framework provides effective land management and land use planning, thus enhance rural sustainability in the Yobe state, Nigeria. The study recommends review land inheritance laws and other laws regarding communal land allocation and ownership to resolve land fragmentation and population control in Yobe state.